Efecto de la inclusión parcial de dos niveles de harina de algarrobo (Prosopis chilensis) en el hemograma y bioquímica sanguínea en pollos Cobb 500 - Franco Anzules, Juan José (2021)
The objective of this research was the comparison of the effect of the partial inclusion of two levels of carob flour (Prosopis chilensis) in the blood count and blood chemistry in Cobb 500 chickens. It was subjected to a completely randomized design for days 21 and 42, having as the only factor the two levels of carob (15%, 25%). For the study of the data, the analysis of variance was used through the statistical package InfoStat (2019) alpha value of 5%. For the hemogram analysis on days 21 and 42, only significant differences (p <0.05) were found for mean corpuscular volume on day 21, where t2 (25%) obtained the lowest average (122.83 mg / dl). For the blood biochemistry analysis on day 21, a significant difference was found for triglycerides (p <0.05), t1 (15%) obtained the lowest level with 96.11 mg / dl and for bilirubin, the highest level was obtained t0 (0%) with 0.92 mg / dl. For day 42, significant differences were found (p <0.05), in triglycerides and direct bilirubin, with the lowest values in t2 (25%) (122.80 mg / dl and 0.22 mg / dl). Likewise, for urea and albumin (p <0.05), t 0 (0%) obtained the lowest parameter (24.35 mg / dl) of urea and the highest level of albumin (24.35 mg / dl). The results allow us to conclude that adding 15% of carob flour, in the diet of Cobb 500 broilers, reduces triglycerides and direct bilirubin levels, promoting the proper physiological functioning of the liver.